2020
DOI: 10.1136/emermed-2019-208721
|View full text |Cite
|
Sign up to set email alerts
|

Routine alcohol screening in the ED: unscreened patients have an increased risk for hazardous alcohol use

Abstract: BackgroundRoutine screening programmes for hazardous alcohol use in the ED miss large numbers of patients. We investigated whether patient-related or staff-related factors cause screening failures and whether unscreened patients are at increased risk of hazardous alcohol use.MethodsThis is a secondary analysis of a prospective study. From November 2012 to November 2013, all adult patients visiting a Dutch inner city ED were screened for hazardous alcohol consumption using the Alcohol Use Disorders Identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In clinical settings, it is practically difficult to screen all patients for alcohol use. One study has used AUDIT-C for all patients visiting the emergency room for 1 year and found that only 65% of patients are screened (61). It was found that 25% of patients did not undergo such screening because their medical staff forgot to ask questions about alcohol and 8.8% of patients struggled with questions or refused to cooperate.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical settings, it is practically difficult to screen all patients for alcohol use. One study has used AUDIT-C for all patients visiting the emergency room for 1 year and found that only 65% of patients are screened (61). It was found that 25% of patients did not undergo such screening because their medical staff forgot to ask questions about alcohol and 8.8% of patients struggled with questions or refused to cooperate.…”
Section: Discussionmentioning
confidence: 99%
“…Of 28,019 patients, 65% were screened, and 35% were not. Failures to screen included patient refusal to cooperate due to pain, illness, intoxication, decreased level of consciousness, neurological deficits, language barriers, and acute mental illness (van Loon et al, 2020). Patients who were not screened were either unwilling or unable to participate.…”
Section: Avoidance Biasmentioning
confidence: 99%
“…Researchers found that male patients, alcohol-related visits, trauma, and head injuries were independently associated with a lack of screening. Patients at the highest risk for HAU were most often unscreened (van Loon et al, 2020). The importance of conducting repeat screening, flagging patients who were not screened, receiving prompts through the electronic medical record (EMR).…”
Section: Avoidance Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol has also increased traffic accidents, trauma [ 6 ], absenteeism [ 7 ] at the workplace and school [ 8 ], job loss, violent behavior, and legal [ 9 ], family, economic, mental [ 10 ], and social problems [ 5 ]. Despite the significant benefits of alcohol abuse treatments [ 11 ], general practitioners only manage to diagnose a third of these patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%